2006
DOI: 10.1536/ihj.47.763
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate ICD Therapy in Patients With Idiopathic Dilated Cardiomyopathy Long-Term Follow-Up

Abstract: SUMMARYThe implantable cardioverter defibrillator (ICD) has proved effective in preventing sudden death and decreasing mortality in randomised secondary prevention trials. Some nonrandomised studies have reported different incidences and predictors of appropriate ICD therapy in patients with idiopathic dilated cardiomyopathy (DCM). The antiarrhythmic and other medical therapies were different between the published studies and it was reported that not using beta-blockers was a predictor of appropriate ICD thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…[13][14][15][16] Our relatively high incidence of adequate ICD intervention may be explained in part by the high number of nsVT in our primary preventive ICD recipients. Although in this study nsVT were not predictive for arrhythmias there might have been a selection bias due to the small sample rate.…”
Section: Arrhythmias In Dilated Cardiomyopathymentioning
confidence: 97%
“…[13][14][15][16] Our relatively high incidence of adequate ICD intervention may be explained in part by the high number of nsVT in our primary preventive ICD recipients. Although in this study nsVT were not predictive for arrhythmias there might have been a selection bias due to the small sample rate.…”
Section: Arrhythmias In Dilated Cardiomyopathymentioning
confidence: 97%
“…There were no differences in the cardiovascular mortality and all-cause mortality between the ICM patients and DCM patients receiving ICD for secondary prevention. After adequate medical treatment for at least half a year half-year adequate medical treatment, a higher prevalence of recurrent ventricular tachyarrhythmia was noted in the patients with LVEDV > 158 mL One study reported that around 50 % of recurrent VT/VF events developed in DCM patients with ICD implantation for primary prevention and secondary prevention, and the time between implantation and first appropriate therapy was similar between primary and secondary prevention patients (Karaoguz et al, 2006;Meyer et al, 2009). LV dilatation has been reported to be as a major negative prognostic marker in patients with HF (Frigerio et al, 2005) and indicates a diseased heart with a high posibility of recurrent ventricular tachyarrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Concernant les antitarythmiques, ceux de la classe III de la classification de Vaughan Williams (amiodarone, sotalol, dofétilide, azimilide) sont particulièrement recommandés car ils ont des effets bénéfiques sur les fréquents chocs induits par les DAI chez des patients qui en sont porteurs [7, 8], tel était le cas de notre patient. Aussi, les antiarythmiquessont considérés comme nécessaires chez plus de 70% des patients porteurs de DAI pour plusieurs raisons [7]: ils permettent de prévenir et traiter les épisodes de tachyarythmies atriales (la fibrillation atriale étant l’arythmie la plus fréquente, survenant chez plus de 20% de patients porteurs d’un DAI) [7]; les antiarythmiques contribuent à diminuer la fréquence des chocs des DAI; enfin, ils permettent de juguler les arythmies ventriculaires résultant des traitements par stimulation antitachycardique (ATP) délivrés par les DAI.…”
Section: Discussionunclassified